Pott's Disease in a Young Child - Parvin, R; Haque, MA; Islam, MN; Shaha, CK; Uddin, SN; Sarkar, S; Hossain, MB (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jul;17(2):206-9.The abstract of this article is available on the PubMed website